Climatic suitability and potential distribution of earleaf acacia and its candidate biological control agent Trichilogaster sp - Sara S. MacDonald; Emily J. Le Falchier; Lindsay P. Campbell; Ryan Zonneveld; Carey R. Minteer (Biological Control)
Acacia auriculiformis A. Cunn. ex Benth. (Fabaceae), commonly known as earleaf acacia (ELA), is an invasive evergreen tree introduced to the USA from its native subtropical forests in Australia, Papua New Guinea, and Indonesia. Since its introduction to the United States in the 1930s, ELA has spread across Florida and Hawaii, and it has the potential to invade further climatically suitable regions. This study utilizes ecological niche modeling (ENM) to predict the potential distribution of ELA across the Caribbean, Central America, and North America, and assess the climatic suitability of Florida for the candidate biological control agent, Trichilogaster sp. nov., a gall-forming wasp. Earleaf acacia occurrence data were sourced from surveys and databases and Trichilogaster sp. nov. occurrence data were sourced from native range surveys. Ecological niche models were created using the ‘maxnet’ algorithm in the ‘ENMEval’ R package with appropriate environmental variables. The results indicate that a variety of regions across the Americas, including Florida and Louisiana in the United States, as well as Mexico, Belize, Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica, and Panama have climates suitable for ELA. For Trichilogaster sp. nov., the model forecasts suitable climatic conditions in southern Florida and along the east coast of the USA. Both models exhibit high predictive accuracy, with AUC values above 0.9. This study emphasizes the need for continued monitoring and management of ELA and evaluates areas in Florida predicted to have suitable climatic conditions for Trichilogaster sp. nov. If it is approved for release as a biocontrol agent in Florida. Our findings contribute to understanding the potential distribution of ELA in North America and offers insights into potential management strategies using its co-evolved natural enemy Trichilogaster sp. nov as a biological control agent.